Analysis of Edible Oil Oxidation Based on Changes in the Electrical Conductivity of the Extracted Aqueous Phase. Issue 5 (3rd April 2019) - Wang, Mengzhu; Huyan, Zongyao; Jing, Bingyu; Mao, Xiaohui; Yu, Xiuzhu
Abstract : A novel and rapid method is developed to analyze oxidation in edible oils by using electrical conductivity (EC). The extent of edible oil oxidation is confirmed using the American Oil Chemists' Society (AOCS) standard method as a reference. Analytical conditions, including temperature, oscillating time, and water–oil (v/v) ratio, are optimized to determine ECs. A model is established based on EC changes in the aqueous phase extracted from several water–oil mixtures. This model is used to predict the oxidation degree of the samples, and its results are validated by the AOCS standard methods. Results show that the analytical conditions exert no significant effects on EC determination. The model is developed using a water–oil (v/v) ratio of 5. Three regions are classified according to the ECs of the samples. Oils with ECs less than 6.9 µS cm −1 are found to be non‐oxidized oils, samples with ECs within 6.9–8.9 µS cm −1 are suspected oils, and samples with ECs exceeding 8.9 µS cm −1 correspond to oxidized oils. The total identification rate of the model in validation samples is 94.1%. The results of the present study clearly indicate that the proposed method can be used as an alternative to conduct qualitative discrimination of the oxidation degree of edible oils. Practical applications : A method based on EC changes in the aqueous phase is used to determine the extent of edible oil oxidation. A total of 151 oil samples are used and assigned to two groups for calibration ( n  = 83) and validation ( n  = 68) oil samples. In the EC method, determination of ECs is independent of analytical conditions, which provides great flexibility in the selection process. The method requires no spectral pre‐treatments or data processing methods, which simplifies the experiment process. Furthermore, the EC instrument is less than 40 $ USD, which is more affordable and portable in a small scale. These characteristics make the proposed method convenient for inspection departments to accomplish on‐site testing of edible oils. The EC method can be applied to determine edible oil oxidation. A method based on EC changes in the aqueous phase extracted from water–oil mixture is used to determine the extent of edible oil oxidation. At a water–oil (v/v) ratio of 5, the EC model can be divided into three regions: ECs of less than 6.9 µS cm −1 representing non‐oxidized oils, ECs within 6.9–8.9 µS cm −1 representing suspected oils, and ECs of over 8.9 µS cm −1 representing oxidized oils. The total identification rate of the model in validation samples is 94.1%. Abstract : A method based on EC changes in the aqueous phase extracted from water–oil mixture is used to determine the extent of edible oil oxidation. At a water–oil (v/v) ratio of 5, the EC model can be divided into three regions: ECs of less than 6.9 µS cm −1 representing non‐oxidized oils, ECs within 6.9–8.9 µS cm −1 representing suspected oils, and ECs of over 8.9 µS cm −1 representing oxidized oils. The total identification rate of the model in validation samples is 94.1%.